Russia and the Napoleonic Wars
XVII, 271 p. 5 illus.
Keywords: Russia played a fundamental role in the outcome of Napoleonic Wars; the wars also had an impact on almost every area of Russian life. Russia and the Napoleonic Wars brings together significant and new research from Russian and non-Russian historians and their work demonstrates the importance of this period both for Russia and for all of Europe.